Legal Analysis of Land Certificate Management in Sidomulyo Village, Ampel District, Boyolali Regency - Carmadi, Aris; Destyarini, Normalita; Nugrahaningsih, Widi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this research was to find out what the legal analysis about processing land certificates in Sidomulyo Village, Ampel District, Boyolali Regency and the process was in processing land certificates at the National Land Agency (BPN) Boyolali Regency in the Sidomulyo Village area, Ampel District. This research was a type of normative legal research. From an etymological perspective, normative legal research is also called legal research, normative legal research, or normative juridical onderzoek. Normative legal research is legal research, which legal analysis through concepts, norms, or rules that exist in society and became a reference for everyone's behavior. When viewed from the legal aspect, the implementation of land certification in the Sidomulyo village area refered to UUPA no. 5 of 1960 which is the most basic legal basis regarding land certification to date, and PP No. 24 of 1997 concerning Land Registration which regulates the process of land registration/certification by government bodies whose task is to record mapping of community land and its ownership status. The process of issuing land certificates in Sidomulyo Village, Ampel District, Boyolali Regency carried out by the National Land Agency (BPN) of Boyolali Regency was considered smooth and controlled. For residents of Sidomulyo Village, the issuance of land deeds functions as legal guarantee for owners of assets in the form of land